Efeito do exercício físico no miocárdio de ratas durante prenhez e lactação submetidas ao tabagismo passivo - Araujo, Bruna Corral Garcia de (2017)
Passive smoking is recognized as a risk factor for cardiovascular disease (CVD). Physical exercise has been widely pointed out to prevent and treat CVD; taking into account that regular practice provides beneficial metabolic, neuromuscular and cardiovascular changes for both mother and fetuses. Objectives – To evaluate the impact of physical exercise through swimming during the period of pregnancy and lactation, with morphometric, cariometric and fractal dimension analyses of the myocardium in rats submitted to passive smoking, and their offspring considering, in this case, body and heart weight, as well as in the mothers. Material and Methods – Forty-eight female rats divided into eight groups were studied; four of them pregnant: GFP - exposed to cigarette smoking; GFNP - cigarette smoking and swimming; GNP - just swimming; GCP – control; and other four groups with pregnancy and in lactation: GFL - exposed to cigarette smoking; GFNL - cigarette smoking and swimming; GNL - just swimming; GCL - control. During pregnancy and lactation, the protocol for cigarette smoking exposition was 30 minutes twice a day for six weeks. At this same period, the swimming program was started for 60 minutes a day up to the 21st day of breastfeeding. Body weight of all animals was recorded at the end of the experiment. After euthanasia, the heart of mothers and their offspring were weighed, and the mothers’ myocardium also submitted to histomorphometric analysis with measurement of the cardiomyocyte area; cariometry and fractal dimension. P-value<0.05 was used for significance value. Results - After the lactation period, the group GNL showed increase in body weight as compared to those exposed to the swimming protocol associated to cigarette smoking (GFNL; P=0.026). In relation to offspring, the offspring of mothers exposed to smoking and swimming (GFNP) showed reduction in body weight (22.547±4.68g) as compared to the offspring of mothers exposed to smoking (GFP: offspring = 26.452±4.59g; P=0.003) and to the group without exposure and not included in the swimming program (GCP: offspring = 34.47±7.81g; P=0.001). GFNP offspring also presented reduced values in heart weight (0.157±0.027g) as compared to the offspring of mothers exposed to swimming (GNP: offspring=0.251±0.033g; P=0.004). There was an increase in the area of cardiomyocytes in pregnant rats exposed to cigarette smoking and to the swimming protocol (GFNP: median=267.74μm2) as compared to pregnancy only (GCP=252.97μm2; P=0.044), as well as to the group submitted to the swimming protocol (GNP=251.48μm²; P=0.022). During pregnancy and lactation period, the group exposed to swimming protocol (GNL) was stood out with increased values of the area of cardiomyocytes (290.08μm2) as compared to the group of the swimming and passive smoking program (GFNL=241.96μm²; P<0.0001). Cariometry and fractal dimension showed no difference between the groups (P>0.05). Conclusion – Passive smoking associated with swimming during pregnancy and lactation period influences the reduction of body weight in female rats as well as the offspring, that also presents a reduction in heart weight. On the other hand, the swimming practice during both periods influences cardiac muscle hypertrophy in rats, even in exposure to passive smoking during pregnancy, suggesting maintenance of the contractile performance of the heart.